Diffusion tensor imaging of sequential neuropathological patterns in progressive supranuclear palsy - Bârlescu, Lavinia A.; Höglinger, Günter U.; Volkmann, Heiko; Ludolph, Albert C.; Del Tredici, Kelly; Braak, Heiko, the DESCRIBE-PSP Study Group; Müller, Hans-Peter; Kassubek, Jan; Brandt, Moritz; Buerger, Katharina; Düzel, Emrah; et al. (Frontiers in Aging Neuroscience, 2025)
Background and objectiveA neuropathological cerebral staging concept for progressive supranuclear palsy (PSP) has been proposed that tau inclusions in PSP may progress in a sequential regional pattern. The objective was to develop a hypothesis-guided region/tract of interest-based (ROI/TOI) approach to use diffusion tensor imaging (DTI) targeted to analyze in vivo the regions that are prone to be involved at each neuropathological stage of PSP.MethodsTwo data cohorts were analyzed: cohort A of 78 PSP patients [55 Richardson’s syndrome (PSP-RS) and 23 PSP with predominant parkinsonism (PSP-P)] and 63 controls, recorded at 3.0T at multiple sites, and a single-site cohort B constituted by 1.5T data of 66 PSP patients (46 PSP-RS and 20 PSP-P) and 44 controls. In cohort A, 21 PSP patients (13 PSP-RS and 8 PSP-P) and 17 controls obtained a follow-up scan after 17 months. Whole brain-based spatial statistics (WBSS) was used to identify the alterations in PSP patients vs. controls. The combined ROI- and TOI-based approach targeted structures that are prone to be involved during the course of PSP.ResultsWBSS demonstrated alterations predominantly in brainstem/midbrain, basal ganglia, and frontal lobe, more pronounced in the longitudinal data. Statistical analyses of the ROIs/TOIs showed a sequential pattern of structures that were assigned to previously defined neuropathological steps.ConclusionThe combined ROI- and TOI-based DTI approach was able to map the disease stages of PSP in vivo cross-sectionally and longitudinally, lending support to DTI as a technical marker for imaging disease progression according to PSP stages. This approach might be useful as a tool for stratification of PSP patients MRI with respect to its proposed neuropathological progression in future longitudinal and autopsy-controlled studies.